2019
DOI: 10.3390/ijerph17010177
|View full text |Cite
|
Sign up to set email alerts
|

The Dose of Fungal Aerosol Inhaled by Workers in a Waste-Sorting Plant in Poland: A Case Study

Abstract: Bioaerosol monitoring is a rapidly emerging area in the context of work environments because microbial pollution is a key element of indoor air pollution and plays an important role in certain infectious diseases and allergies. However, as yet, relatively little is known about inhaled doses of microorganisms in workplaces. Today, the important issue of social concern is due to waste management, transport, sorting, and processing of wastes and their environmental impact and effects on public health. In fact, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…A previous study reported that Aspergillus spp. caused aspergillosis and allergic aspergillosis syndrome [11,[46][47][48]. A study on concentrations of airborne microorganisms indicated that most fungi were found in a food center (Penicillium spp., Aspergillus spp., and Cladosporium spp.)…”
Section: Concentrations Of Gram-positive and Gram-negativementioning
confidence: 99%
“…A previous study reported that Aspergillus spp. caused aspergillosis and allergic aspergillosis syndrome [11,[46][47][48]. A study on concentrations of airborne microorganisms indicated that most fungi were found in a food center (Penicillium spp., Aspergillus spp., and Cladosporium spp.)…”
Section: Concentrations Of Gram-positive and Gram-negativementioning
confidence: 99%
“…Fungal growth on indoor surfaces has been associated with health problems in dwelling occupants [ 15 ] through the aerosolisation of fungal particles [ 16 ]. Indeed, spores, hyphal fragments and microbial volatile organic compounds (mVOCs) can be emitted from mouldy surfaces [ 17 ] and the size of these particles is small enough to be inhaled [ 16 , 18 , 19 ]. A chronic exposure to moulds can induce a hypersensitivity in healthy adults [ 20 ], as well as respiratory problems such as asthma in young children [ 21 , 22 , 23 ], adults [ 24 ] and older adults [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of bioaerosols on human health is not only related to their concentrations. The aerodynamic diameters of bioaerosols determine their potential to be deposited either in the tracheal, bronchial, or alveolar regions of the lungs, so their size distribution is also important [20,34]. The use of the six-stage Andersen impactor allowed us to obtain data on the grain distribution of micro-organisms and to determine how deeply they penetrate the respiratory system of power plant workers.…”
Section: Particle Size Distribution (Psd) Of Bioaerosolsmentioning
confidence: 99%
“…Infectious agents for most of the diseases listed above are transmitted by air. The most common ailment caused by various types of air pollution is allergy (an excessive reaction of the body to the presence of allergens), in which large amounts of antibodies are produced [20].…”
Section: Introductionmentioning
confidence: 99%